Implementation of The Auction Execution of Mortgage Objects (Case Study at the State Asset and Auction Service Office of Malang) - Septyana, Ade (Fakultas Hukum Universitas Islam Malang, 2025)
The execution auction of mortgaged objects in the concept of parate execution, carried out at the State Aset and Auction Service Office of Malang, doesn’t always proceed smoothly due to uncooperative debtors, which hampers the auction process. The urgency of this research is to examine the legal certainty of auction processes in the face of obstacles. The purpose of this research is to analyze the factors that hinder the auction process and the efforts made to overcome these obstacles. This empirical study uses a sociological approach with primary and secondary data sources. Obstacles to the auction process include incomplete documents, failure to find a buyer, low reserve price, difficulty in vacating the object, and ongoing lawsuits. The efforts to overcome these obstacles involve seeking information, re-auction, negotiating the reserve price, issuing the grosse minutes of auction, sending an aanmaning, pursuing non-litigation methods, and applying evidentiary theory.